2022
DOI: 10.3390/ma15093129
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Synthesized CoO/Co3O4 Nanoparticles as A Corrosion Inhibitor of Low-Carbon Steel in 1 M HCl

Abstract: CoO/Co3O4 nanoparticles (CoO/Co3O4 NPs) were synthesized with egg white. The effectiveness of CoO/Co3O4 NPs to inhibit the corrosion of carbon steel has verified in acidic medium (1 M HCl). It has been found that Langmuir adsorption isotherm is the dominant adsorption process of CoO/Co3O4 NPs on the surface of low-carbon steel. The thermodynamic parameters also demonstrated that the adsorption process of CoO/Co3O4 NPs was a physicochemical, spontaneous, and exothermic process. The electrochemical impedance spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The outer layer was composed of relatively large and loose spinel particles, while the inner layer was composed of relatively small and compact spinel particles. The particles on the 304SS exhibited the spinel structures of Co(Fe, Cr) 2 O 4 , but not CoO, Co 2 O 3 , Co(OH) 2 , or CoOOH [ 39 , 40 , 41 , 42 ]. In the studies by Hetache et al [ 43 ] and Ebrahimifar [ 44 ], it was reported that the CoFe 2 O 4 and CoCr 2 O 4 particles exhibited spinel shapes.…”
Section: Discussionmentioning
confidence: 99%
“…The outer layer was composed of relatively large and loose spinel particles, while the inner layer was composed of relatively small and compact spinel particles. The particles on the 304SS exhibited the spinel structures of Co(Fe, Cr) 2 O 4 , but not CoO, Co 2 O 3 , Co(OH) 2 , or CoOOH [ 39 , 40 , 41 , 42 ]. In the studies by Hetache et al [ 43 ] and Ebrahimifar [ 44 ], it was reported that the CoFe 2 O 4 and CoCr 2 O 4 particles exhibited spinel shapes.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, the organic compounds examined included three surfactants: Brij 35 (polyethyleneglycol (23) lauryl ether, C12H26 (CH2CH2O)23OH), Brij 56 (polyethyleneglycol (10) monocethyl ether, C16H33(CH2CH2O)10OH), and Brij 58P (polyethyleneglycol (20) hexadecyl ether C16H33 (CH2CH2O)20OH) (Scheme 1) were produced from Sigma-Aldrich of pure quality (>98%). The 0.5 M H2SO4 aggressive environment was made by diluting 97% H2SO4 (AG, Merck, Darmstadt, Germany) with bidistilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Since corrosion is the considerable agent in the deterioration of manufacturing constituents, many experiments were conducted to discover mechanisms to reduce corrosion and wear expenses. Protection against the corrosion of these metallic materials can be accomplished using several techniques, among which the treatment of corrosive environments through the application of inhibitors is a significant procedure [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Numerous investigations performed for the defense of metals used in technological domains have divulged that it is a very efficacious and simple application to utilize organic inhibitors to impede the deterioration of metals in aggressive environments [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most often used transition metal oxides is cobalt oxide (Co 3 O 4 ) nanoparticles because of their relatively high electrochromic efficiency (25 cm 2 C −1 ), large surface area, strong conductivity, and enhanced electrochemical stability 4 . Cobalt oxide alone or in mixed form is used as protective thin film under different temperatures and pressures 5 7 .…”
Section: Introductionmentioning
confidence: 99%